Socioscope: Human Relationship and Behavior Analysis in Social Networks - Zhang, Huiqi; Ram Dantu; Cangussu, João (IEEE Transactions on Systems, Man, and Cybernetics - Part A: Systems and Humans, 2011)
In this paper, we propose a socioscope model for social-network and human-behavior analysis based on mobile-phone call-detail records. Because of the diversity and complexity of human social behavior, no one technique will detect every attribute that arises when humans engage in social behaviors. We use multiple probability and statistical methods for quantifying social groups, relationships, and communication patterns and for detecting human-behavior changes. We propose a new index to measure the level of reciprocity between users and their communication partners. This reciprocity index has application in homeland security, detection of unwanted calls (e.g., spam), telecommunication presence, and product marketing. For the validation of our results, we used real-life call logs of 81 users which contain approximately 500 000 h of data on users' location, communication, and device-usage behavior collected over eight months at the Massachusetts Institute of Technology (MIT) by the Reality Mining Project group. Also, call logs of 20 users collected over six months by the University of North Texas (UNT) Network Security team are used. The MIT and UNT data sets contain approximately 5000 callers. The experimental results show that our model is effective.
Keywords: behavioural sciences computing; Change points; communication pattern; Data models; human relationship analysis; human social behavior; human-behavior change detection; Humans; IEEE; Massachusetts Institute of Technology; Mobile handsets; probability; Reality Mining Project group; reciprocity index; Social factors; social group; social groups; social network analysis; Social network services; social networking (online); Social networks; social relationship; social relationships; social sciences computing; socioscope; Statistical analysis; statistical method; University of North Texas

Socio-technical aspects of video phones - Chandrasekaran, Vikram; Dantu, Siva; Kadiyala, Priyanka; Ram Dantu; Phithakkitnukoon, Santi (2010 Second International Conference on COMmunication Systems and NETworks (COMSNETS 2010), 2010)
The widespread use of voice over Internet protocol has paved the way for video over Internet protocol. In the past, certain technical shortcomings have prevented the popularity of videophones in the market. With present-day technology, videophones have just about everything required for day-to-day functions. Under such circumstances, certain socio-technical aspects require attention so that videophones can become as widespread and as technically streamlined as a plain old telephone system (POTS) with its additional benefits. A frequently brushed-upon topic is optimum features in the video phone for day-to-day social interactions. We carried out several experiments on different kinds of codecs and video formats to address two issues: i) the size of a video screen and ii) perception of motion and distance. From the measurements, we observed that a small frame rate with low bandwidth is adequate and can result in satisfactory video quality. We also observed that H263 performs well for all the day-to-day social networking activities. Standing 4 feet from the camera can still give reasonably good video quality in the currently available codecs. We believe that socio-technical issues will emerge more clearly over the next several years and they are germane to deployment of PC-based soft phones as well as hard phones.
Keywords: Bandwidth; Cameras; Codecs; Computer science; Internet telephony; plain old telephone system; Protocols; social aspects of automation; Social factors; social interactions; social issues; Social network services; social networking activities; sociotechnical aspects; Streaming media; technical issues; video codecs; video coding; video phones; video quality; Videoconference; videophone quality; videophones; videotelephony; voice over Internet protocol

A society-integrated testbed architecture for peer-to-peer telecommunications - Yang, Xiaohui; Ram Dantu; Wijesekera, Duminda (Testbeds and Research Infrastructures for the Development of Networks Communities and Workshops, 2009. TridentCom 2009. 5th International Conference on, 2009)
Exploiting and deploying telecommunication services on Internet Telephony are imperative for a large market share. However, the distributed nature of peer-to-peer (P2P) network makes services implementation very difficult. In order to meet the research goals of achieving P2P telecommunication services through the union of social and computer networks, we present a society-integrated testbed architecture for P2P voice over IP (VoIP). By introducing an architecture that exploits and entailing social structure based connection establishment, the testbed presents an organic integration of social functionalities with good portability. The testbed also serves as a flexible tool suite that can be used to run experiments and obtain timely feedback based on the performance measurements.
Keywords: Computer architecture; computer network; computer networks; Computer science; Feedback; file organisation; Internet telephony; network traffic; P2P voice-over-IP; Peer to peer computing; peer-to-peer computing; peer-to-peer telecommunication service; portable social DHT function; Routing protocols; Social network services; society-integrated testbed architecture; software architecture; Telecommunication services; telecommunication traffic; Testing

A testbed for mobile social computing - Alazzawe, Ahmed; Alazzawe, Anis; Wijesekera, Duminda; Ram Dantu (Testbeds and Research Infrastructures for the Development of Networks Communities and Workshops, 2009. TridentCom 2009. 5th International Conference on, 2009)
We present a testbed for mobile social computing that can be used to perform research in security, privacy, and context-awareness policies and mechanisms appropriate for a wide range of applications. We compare several mobile platforms and present the rational for our design choices and reasons we chose Android as the primary smartphone for this testbed. We also discuss some of the possible experiments that can be conducted using the testbed.
Keywords: Acoustic sensors; Computer science; Computer security; context-awareness policy; data privacy; Feedback; Global Positioning System; mobile computing; mobile social computing; Performance evaluation; Privacy; privacy policy; security of data; security policy; Social network services; Testing

Call Algebra - Kolan, Prakash; Ram Dantu (2008 5th IEEE Consumer Communications and Networking Conference, 2008)
In every day life, people communicate through a voice(e.g., VoIP) network with different social groups that range from known people such as family members, friends, and distant relatives to unknown people such as spammers, telemarketers, and phishers. We believe that there exists a human/social dynamics between individuals by the way calls are generated, handled and received. In this paper we present how this dynamics can be used for detecting and filtering unwanted calls. In this paper, we first enumerate the communication patterns between the called party (callee) and the calling parties (callers). Next, we discuss operations on caller-callee matrices constructed based on their communication patterns, and derive call-constructs that can be used for determining the legitimacy of the calls and the callers. Finally, we discuss how these communication patterns and operations can be grouped for solutions to few of the existing IP telephony problems. These solutions can complement the existing no-call-lists in voice networks.
Keywords: Algebra; call algebra; caller-callee matrices; communication pattern; Computer science; Context modeling; Filtering; Humans; Internet telephony; IP networks; IP telephony problem; matrix algebra; Mood; Peer to peer computing; social aspects of automation; social group; Social network services; voice-over-IP; VoIP network